Pengaruh Sari Bawang Merah (Allium cepa L) Terhadap Volume Getah Karet(Hevea brasiliensis L) di Desa Bangun Rejo Kecamatan Bilah Hilir - Putra Hakiki; Badrul Ainy Dalimunthe; Novilda Elizabeth Mustamu (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2023)
Rubber (Havea brasiliensis L) is one of the important plantation commodities, both as a source of income, job opportunities and foreign exchange, as a driver of new economic growth in the area around rubber plantations as well as environmental and biological resource conservation.The purpose of this study was to determine the concentration of the effect of using shallot juice (Allium cepa L.) to increase the volume of rubber latex (Hevea brasiliensis L). This research was conducted in the rubber plantation field in Bangun Rejo Village, Bilahilir District, using the Non-Factorial Experimental method and 3 replications.The data obtained were analyzed using a variance test and continued with the Duncan distance test. The results showed that the application of shallot juice with a concentration of 100% had a significant effect on the production of rubber latex. Further research is needed to determine the effect of onion juice on other plants with high economic value.Keywords : Rubber (Havea brasiliensis L), Shallot (Allium cepa L.)